Metabolic Abnormalities in Abstinent Methamphetamine Dependent subjects - Napapon Sailasuta; Osama Abulseoud; Martha Hernandez; Poone Haghani; Brian D Ross (Substance Abuse: Research and Treatment, 2010)
Introduction Chronic methamphetamine use results in persistent neuropsychological deficits in abstinent methamphetamine dependent (AMD) subjects. We examined the hypothesis that elevated concentration of cerebral glutamate (Glu), an excitatory neurotransmitter and neurotoxin, occurs in human AMD. Materials and Methods We examined 40 subjects, 18 of whom were AMD, abstinent more than 3 weeks and 22 were age matched controls. A Structured Clinical Interview was applied to exclude AMD with comorbid depression. We used TE-Averaged technique of MRS to uniquely identify and quantify the glutamate resonance at 2.35 ppm on a 3T clinical MR scanner. Statistics, including Bonferroni correction for multiple MRS variables were applied. Results Glu was significantly higher in frontal white matter of AMD (+19%, P = 0.01) and N-acetylaspartate (NAA), an axonal marker, was lower (-14%, P = 0.004). No significant MRS abnormalities were detected in posterior gray matter. Significant correlations were observed between NAA and Glu ( P = 0.002 for AMD and P = 0.06 for controls in the posterior gray matter and P = 0.01 for controls and not significant for AMD in the frontal white matter). Conclusion Our results demonstrate a significant excess of glutamate in frontal white matter of AMD subjects and offer support for the hypothesis that methamphetamine abuse may exert its long-term neuro-toxicity via glutamate.